Time–Cost Trade-off Analysis in a Construction Project Using Mixed Integer Linear Programming: A Case Study - NAWAWRAH, ABDULRHMAN (İstanbul Kültür Üniversitesi, 2022)
The issue of the trade-off between time and cost when scheduling building projects under some constraints such as the final project delivery date, the budget allocated to the project, etc. is one of the most important problems that have been analyzed by a lot of research. Therefore, most studies in TCTP target to finish the project on time without exceeding the budget. This goal can only be reached by speeding up some activities to shorten the overall project duration. This, in turn, is reflected in the cost of the activities, increasing the total cost of the project. As project management has become more complex because of advances and capabilities in the latest building technologies, researchers have sought to develop a complete and flexible mathematical scheduling model to deal with project constraints. This thesis presents a convenient and practical solution approach for the creation of the schedule, that will enable engineers and project managers to get the best return on the project in the shortest possible time and at the lowest possible cost. The critical path of the activities was determined using CPM and PERT methodologies, and the findings were validated using Monte Carlo simulation. The TCTPS problem is solved using MS Excel Solver, utilizing the resulting mixed-integer linear programming approach, assuming resources are available and unlimited. The developed approach was applied to a real-world application, namely the luxury villa construction project.
İnşaat Projelerinin Çizelgelenmesinde Zaman-Maliyet Ödünleşme Problemlerinin Karışık-Tamsayı Programlama İle Optimize Edilmesi: Bir Vaka Çalışması
▪ Yüksek lisans tezi.